Training and Development System Analysis at PT. Perkasa Beton Batam - Azzahra, Deta Hafiz; Dihan, Fereshti Nurdiana (Selekta Manajemen: Jurnal Mahasiswa Bisnis & Manajemen, 2023)
Every company has its efforts to improve employee performance capabilities, one of which is through training, development, and attitude improvement. However, many companies have yet to pay attention to the system’s effectiveness in its implementation, so it needs to be evaluated further. This study aims to identify the training and development system at PT. Perkasa Beton Batam. Descriptive research designs with qualitative variety are used. The study was conducted by interviewing the HRT team and three staff members to identify research variables. Structured interviews are conducted and analyzed descriptively. The results show that the PT. Perkasa Beton Batam training program is carried out by classroom and lecture methods. The classroom method is used when the material presented is theoretical and needs focus and understanding from participants. The lecture method, or lecturer method, is a method that uses oral techniques by the presenter to deliver special material. Furthermore, the development program is carried out through seminars, learning outcomes, and briefings or discussions attended by all staff and external parties. The evaluation results show that the company’s program design still needs evaluation; participants must perform satisfactorily. Training at this company already provides sufficient returns on the performance of most employees. However, 40% of employees have yet to show good results. Therefore, it is necessary to design a training program that meets the needs of employees and the company—the training system at PT. Perkasa Beton Batam shows an improvement in employee performance, which affects the increase in the percentage of quality targets.